Dancing in the light: six dances by African-American Choreographers - Madison Davis Lacy (New York: The American Dance Festival and Educational Broadcasting corporation)
Awasa Astrige / Ostrich. Barrelhouse blues -excerpt. strange fruit. Mourner's Bench. Rainbow round my shoulder. D-Man in the waters - Section 1 Actores: Talley Beatty, Bill T Jones, Asadata Dafora, Donald Mckayle, Katherine Dunham, Pearl Primus
Area-Documental
Keywords: Genero-Musical